2012
DOI: 10.1016/j.gene.2012.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and leptin receptor genetic variants associate with habitual physical activity and the arm body composition response to resistance training

Abstract: PURPOSE We investigated the influence of Leptin (LEP) and leptin receptor (LEPR) SNPs on habitual physical activity (PA) and body composition response to a unilateral, upper body resistance training (RT) program. METHODS European-derived American volunteers (men=111, women=131, 23.4±5.4 yr, 24.4±4.6 kg·m−2) were genotyped for LEP 19 G>A (rs2167270), and LEPR 326 A>G (rs1137100), 668 A>G (rs1137101), 3057 G>A (rs1805096), and 1968 G>C (rs8179183). They completed the Paffenbarger PA Questionnaire. Arm muscle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 33 publications
2
16
0
3
Order By: Relevance
“…In previous studies with healthy human subjects, e.g., several genetic variations (Riechman et al 2004;Devaney et al 2009;Walsh et al 2012;Van Deveire et al 2012), differences in skeletal muscle gene Raue et al 2012;Phillips et al 2013) and microRNA expression (Davidsen et al 2011), phosphorylation status of signaling proteins (Mayhew et al 2011;Mitchell et al 2013), androgen receptor concentrations (Ahtiainen et al 2011;Mitchell et al 2013), and satellite cell count (Petrella et al 2008) have been suggested to segregate high and low responders to RTinduced muscle hypertrophy. The physiological aspects of individual variation in phenotype responses to RT are apparently very complex phenomena and more studies specifically focused on high and low responders are required to reveal unambiguously the mechanisms of individual differences in RT-induced adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies with healthy human subjects, e.g., several genetic variations (Riechman et al 2004;Devaney et al 2009;Walsh et al 2012;Van Deveire et al 2012), differences in skeletal muscle gene Raue et al 2012;Phillips et al 2013) and microRNA expression (Davidsen et al 2011), phosphorylation status of signaling proteins (Mayhew et al 2011;Mitchell et al 2013), androgen receptor concentrations (Ahtiainen et al 2011;Mitchell et al 2013), and satellite cell count (Petrella et al 2008) have been suggested to segregate high and low responders to RTinduced muscle hypertrophy. The physiological aspects of individual variation in phenotype responses to RT are apparently very complex phenomena and more studies specifically focused on high and low responders are required to reveal unambiguously the mechanisms of individual differences in RT-induced adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…In our prior studies, neonatal leptin administration had robust effects on adult brain volumes, while complementary investigations have shown effects of adult leptin administration on frontal lobe development [13, 17]. Further linking leptin deficiency and locomotor activity are studies by Walsh and colleagues showing an association between leptin or leptin receptor genetic variants and physical activity [32]. The pegylated leptin antagonist utilized in the current investigations allowed potent, sustained central leptin deficiency that, just as importantly, is reversible within days of LX discontinuation [19], implicating postnatal days 4–14 as a critical window of leptin-modulated developmental susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the genetic correlations between leptin and body composition, especially obesity are well known. Several genetic polymorphisms, mapped to a number of genes (e.g., LEP G (‐2548) A, A19G, LEPR G 668A, SERPINF1, and LRP1) have been proposed as possible factors involved in affecting leptin levels and in obesity regulation (Bohm et al, ; Franek et al, ; Smith et al, ; Walsh et al, ). However, the situation with other biochemical factors and body composition is probably even more complex.…”
Section: Discussionmentioning
confidence: 99%